Strengthening Reading and Writing Literacy to Foster Creative Writing Skills at Madrasah Ibtidaiyah - Nasikhotun Nadiroh; Mikyal Hardiyati; Najihah Abd Wahid (Universitas Islam Negeri (UIN) Salatiga, 2024)
This study aims to describe various reading literacy strengthening activities implemented by Madrasah Ibtidaiyah to foster creative writing skills. Using a qualitative research method with a case study approach at MIN 1 Banyumas, data was collected through observation, interviews, and documentation. Data analysis involved reduction, presentation, and conclusion drawing. The findings indicate that teachers strengthen literacy through: 1) mandatory library visits, 2) literacy corners in each classroom, 3) updated wall magazine content, and 4) a daily 15-minute reading program. Writing literacy activities include three stages: 1) pre-writing, 2) writing, and 3) post-writing. In Islamic education, reading and writing are activities with spiritual and intellectual significance, aligning with Islamic values that emphasize knowledge acquisition and dissemination. The study contributes theoretically by expanding the understanding of literacy practices in Madrasah Ibtidaiyah.